2021
DOI: 10.1002/cam4.3790
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor cells detected with a microcavity array predict clinical outcome in hepatocellular carcinoma

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In contrast, positive-enrichment methods take advantage of specific biological and physical properties of CTCs to distinguish them from non-tumoral blood cells. Physical enrichment strategies are frequently based on centrifugation and microfiltration [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] to selectively isolate CTCs according to their differential density and size, respectively [ 51 ]. Among all the positive-enrichment methods, immunoaffinity is the most widely used but the optimal biomarker matching all CTC subpopulations is unknown.…”
Section: Liquid Biopsy and Ctcsmentioning
confidence: 99%
“…In contrast, positive-enrichment methods take advantage of specific biological and physical properties of CTCs to distinguish them from non-tumoral blood cells. Physical enrichment strategies are frequently based on centrifugation and microfiltration [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] to selectively isolate CTCs according to their differential density and size, respectively [ 51 ]. Among all the positive-enrichment methods, immunoaffinity is the most widely used but the optimal biomarker matching all CTC subpopulations is unknown.…”
Section: Liquid Biopsy and Ctcsmentioning
confidence: 99%
“…The chip is composed of a row of posts coated with antibodies. The larger cancer cells collide with the row of posts and stick on as the other cells flow through [33] The OncoCEE ® (Biocept, Inc.)…”
Section: Technology Detection Methods Description Referencesmentioning
confidence: 99%
“…The isolation and capture of CTCs based on biological characteristics of those heterogeneous cells utilize different biological markers expressed in the cells ( Table 2 ) [ 18 , 19 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 45 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. The first data describing the detection and characterization of carcinoma cells in the systemic circulation (bone marrow) based on cytokeratin and MUC-1 glycoprotein expression in epithelial cancer cells, but not in healthy cells, were published 25 years ago [ 63 ].…”
Section: Ctc Isolation and Detection Techniquesmentioning
confidence: 99%
“…Several research groups have successfully developed microfluidic devices for CTC capture. 16,32,40,42,43 For example, Yin et al reported a pyramidal microcavity array (8 μm wide rectangular pores) for CTC capture, and the capture efficiency was about 80%. 42 Negishi et al presented a microcavity array (8 μm wide rectangular pores) that can separate CTCs with a capture efficiency of ∼95%.…”
Section: Introductionmentioning
confidence: 99%